Global Health Governance: Analyzing China, India, and Japan as Global Health Aid Donors - FLORINI, Ann (Institutional Knowledge at Singapore Management University, 2012)
Development assistance is a significant mechanism by which major countries exercise influence in the global health arena. Of the major Asian powers, Japan has long provided significant funding, while China and India have primarily been recipients but are beginning to increase their funding roles. This article examines the amounts, channels, modes, disease allocations and the geographic focuses of their foreign health aid, and delineates the institutional structures that govern the formulation and implementation of foreign health aid policy in each of these countries, to explore what influence China, India, and Japan have and may develop in the global health arena. The article looks in particular at two focal lenses, sovereignty and institutional diversity, to understand what if anything is different from existing approaches to global health governance and what might be expected from these three key Asian nations vis-à-vis global health.